ROLE OF TERMINOLOGICAL COMPETENCE IN TRANSLATION - Dalieva Madina Xabibullaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The study of Terminology in translator training should target the use of terms in real life contexts, and situate these specialized knowledge units within the context of dynamic communication processes. When the meaning and usage of terminological units are analyzed as they appear in texts, oral discourse, and communication situations, it becomes evident that general language and specialized languages are not so very different.